Comparison of surgical and obstetric outcomes in women with uterine leiomyomas after laparoscopic vs. abdominal myomectomy: A single-center cohort study - Ordás, Polán; Spagnolo, Emanuela; Fernández, Lucía Gómez-Lavín; Diestro Tejeda, María Dolores; Lafuente, Pilar; Salas, Patricia; Lopez Carrasco, Ana; Carbonell, María; Hernández, Alicia (Frontiers in Surgery, 2022)
Our aim was to study the advantages, complications and obstetrical outcomes of laparoscopic (LM) compared with abdominal myomectomy (AM). We carried out a retrospective cohort study at La Paz University Hospital included LMs and AMs performed between 2012 and 2018. 254 myomectomies (142 AMs [55.7%] and 112 LMs [43.9%]) were analysed. The mean number of fibroids was 1.8 ± 1.5 and 3 ± 2.9 for LM and AM groups, respectively (p<0.006). The mean size of the largest myoma was 7.6 ± 2.7 cm and 10.2 ± 5.4 cm for LM and AM groups, respectively (p<0.001). LMs showed association with longer surgical time (p<0.001) and shorter hospitalisations (P=0.001). There were no differences in intraoperative and postoperative complication rates (p=0.075 and p=0.285 for LM and AM, respectively). The subsequent pregnancy rate was higher for LM group (30.8% vs. 16.8%, p=0.009), with vaginal delivery rate of 69% and no cases of uterine rupture.